Implementing Precision Medicine: The Ethical Challenges. (January 2017) - Korngiebel, Diane M.; Thummel, Kenneth E.; Burke, Wylie
Abstract : Precision medicine aims to individualize care by understanding differences in genetics, lifestyle, and environment. Pharmacogenomics and cancer genetics represent two promising areas for this approach. Pharmacogenomic tests have the potential to direct drug prescribing to increase safety and effectiveness because individuals vary on a genetic basis in their response to many drugs. Similarly, tests to identify people with an inherited cancer risk can guide prevention. For both, a few tests have entered clinical practice and more are under development. Implementation challenges include the limited evidence base available to guide clinical use and the lack of data from diverse populations. Accordingly, ongoing research should prioritize procedures that enhance the trustworthiness of clinical practice guidelines and create decision support for clinicians and patients that address their needs and accommodate flexibility. Each step involves choices with ethical implications. Trends: Pharmacogenomics and tests for inherited cancer risk are two promising areas of precision medicine. Some genetic tests have entered clinical practice: TPMT and HLA tests to identify individuals at risk for adverse drug response to thiopurines and abacavir, respectively; BRCA1/2 and Lynch syndrome tests to identify increased risk for specific cancers; and tests to diagnose rare genetic conditions. More tests are under development. The evidence base for most genetic tests is limited and lacks data from diverse populations. Trustworthy clinical practice guidelines require systematic evidence review, consideration of all stakeholder views, attention to conflicts of interest, and alignment of the strength of recommendations with the level of evidence available. Promising new approaches to healthcare such as precision medicine have the potential to exacerbate healthcare disparities.